Length-weight relationship and condition factors of Trichogaster pectoralis in the swamp, Lakea Dua Village, Buol Regency, Central Sulawesi - Laheng, Suardi; Adli, Andi; Saum, Rifandi K (Universitas Malikussaleh, 2022)
This study aims to determine the relationship between length and weight and condition factors of Trichopodus trichopterus in the waters of Rawa, Lakea Dua Village, Buol Regency, Central Sulawesi. The research was carried out for 2 months and took place in the swamps of Lakea Dua Village, Buol Regency, Central Sulawesi. The fish collected were measured based on the total length using a ruler in cm (1 mm accuracy), while the fish weight was measured using a digital scale with units of grams (0.01 gram accuracy). The test parameters observed included analysis of length and weight, relative weight, fulcon condition factor, and relative condition factor. The results showed that there were 53 Trichopodus trichopterus collected in the swamps of Lakea Dua Village, Buol Regency. The length ranges from 10-18 cm with an average length of 14.43±2.39 cm. Fish weight ranged from 14.50-155.30 g with an average weight of 51.33±25.83 g. The growth pattern is negative allometric. The relative weight shows a value of 102.63±21.40, meaning that the source of feed is abundant in the Trichopodus trichopterus environment and the condition is healthy. The Fulcon condition factor value is 1.61±0.55 and the relative condition factor is 1.04±0.33, meaning that the condition factor value is below 3. This shows the cheek-shaped fish.Keywords: length weight; condition factor; Trichogaster pectoralis